2008
DOI: 10.1038/ijo.2008.156
|View full text |Cite
|
Sign up to set email alerts
|

Red mold rice prevents the development of obesity, dyslipidemia and hyperinsulinemia induced by high-fat diet

Abstract: Objective: To investigate the influences of red mold rice (RMR) on obesity and related metabolic abnormalities. Methods and results:The 3T3-L1 cell line was used to examine the effects of RMR extracts on preadipocytes and on mature adipocytes. Both water and ethanol extracts of RMR had inhibitory effects on 3T3-L1 preadipocyte proliferation and differentiation. Water extracts of RMR enhanced the lipolysis activity in mature adipocytes, which negatively correlated with the triglyceride content within cells. RMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
47
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 46 publications
7
47
0
Order By: Relevance
“…However, since the energy density of the HF diet was higher than the energy density of the control diet, i.e., 6.57 kcal/g versus 4.17 kcal/g, both groups consumed the same amount of calories. The present data agree with those reported by Chen et al 21 , who also observed a reduced food consumption in animals receiving an HF+ diet compared to control.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, since the energy density of the HF diet was higher than the energy density of the control diet, i.e., 6.57 kcal/g versus 4.17 kcal/g, both groups consumed the same amount of calories. The present data agree with those reported by Chen et al 21 , who also observed a reduced food consumption in animals receiving an HF+ diet compared to control.…”
Section: Discussionsupporting
confidence: 80%
“…Also, Akagiri Akagiri et al 22 , in a 14 week study, did not detect significant differences in weight gain between animals fed the HF diet and controls, although the first one tended to gain more weight. In contrast, Chen et al 21 , after six weeks of study, observed that rats receiving a high-calorie HF diet (22.4% more energy than the control diet) gained more weight than rats receiving a normal diet. The same result was obtained by Matsuzawa-Nagataa et al 23 , after 24 weeks of administration of the HF diet.…”
Section: Discussionmentioning
confidence: 95%
“…The enlargement of this fat depot may be the result of an increase in the number of adipocytes (hyperplasia) or an increase in adipocyte size by lipid accumulation (hypertrophy). Moreover, hyperplasia can be due to the presence of new preadipocytes or to an induction of its differentiation (8). It is known that the most severe form of obesity is characterized by an adipose tissue enlargement as a consequence of adipocyte hyperplasia (18) and that it is related with an early age of onset (10).…”
mentioning
confidence: 99%
“…Many studies have evaluated the potential role of nutraceuticals in the prevention of dyslipidaemia both in animal models (Alshatwi et al, 2011;Chen et al, 2008;Dvir et al, 2009;Huang & Lin, 2012a, 2012b and in humans (Becker et al, 2009;CasasAgustench et al, 2012;Demonty et al, 2006;Dulin et al, 2006;Garaiova et al, 2013;Gonç alves et al, 2006;Guardamagna et al, 2011;Izzo et al, 2010;Maki et al, 2012;Marazzi et al, 2011;Pá rraga et al, 2011;Qin et al, 2009;Rayman et al, 2011;Sirtori et al, 2009;Tomé -Carneiro et al, 2012;Weingä rtner, Bö hm, & Laufs, 2009;Wofford et al, 2012;Wong et al, 2010;Zhao et al, 2011).…”
mentioning
confidence: 99%